2014
DOI: 10.3109/13880209.2014.886273
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and antiproliferative constituents fromDictyota ciliolata, Padina sanctae-crucisandTurbinaria tricostata

Abstract: This study is the first investigation on the bioactive components of D. ciliolata, P. sanctae-crucis, and T. tricostata. Although compounds 1-3 were described previously, the pharmacological activity of compound 4 is presented here for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Pech-Puch et al reported in 2019 the isolation and structural characterization of seven terpenoids from the sponge Spongia tubulifera (now S. (Spongia) tubulifera) that were collected at Rio Indio, Quintana Roo state. Two of them resulted in being new natural products, 3β-hydroxyspongia-13(16),14-dien-2-one (15) and 19-dehydroxy-spongian diterpene 17 (16), while the remaining five corresponded to previously reported terpenes, three spongia furanoditerpenes: 9-nor-3-hydroxyspongia-3,13(16)14-trien-2-one (17), 3β, 19 dihydroxyspongia-13(16),14-dien-2-one (epispongiadiol) (18), and spongian diterpene 17 (19); the furanoditerpene ambliol C (20) and the sesterterpene scalarin (21). The pharmacological analysis of the isolated compounds displayed a very mild cytotoxic activity for 15, 18, and 20, while they showed no antimicrobial (Acinetobacter baumannii, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Staphylococcus aureus) or antiviral (HAdV5 and HAdV5-GFP) activities [16] (Figure 4).…”
Section: Diterpenes and Sesterterpenesmentioning
confidence: 87%
“…Pech-Puch et al reported in 2019 the isolation and structural characterization of seven terpenoids from the sponge Spongia tubulifera (now S. (Spongia) tubulifera) that were collected at Rio Indio, Quintana Roo state. Two of them resulted in being new natural products, 3β-hydroxyspongia-13(16),14-dien-2-one (15) and 19-dehydroxy-spongian diterpene 17 (16), while the remaining five corresponded to previously reported terpenes, three spongia furanoditerpenes: 9-nor-3-hydroxyspongia-3,13(16)14-trien-2-one (17), 3β, 19 dihydroxyspongia-13(16),14-dien-2-one (epispongiadiol) (18), and spongian diterpene 17 (19); the furanoditerpene ambliol C (20) and the sesterterpene scalarin (21). The pharmacological analysis of the isolated compounds displayed a very mild cytotoxic activity for 15, 18, and 20, while they showed no antimicrobial (Acinetobacter baumannii, Pseudomonas aeruginosa, Klebsiella pneumoniae, and Staphylococcus aureus) or antiviral (HAdV5 and HAdV5-GFP) activities [16] (Figure 4).…”
Section: Diterpenes and Sesterterpenesmentioning
confidence: 87%
“…Caamal‐Fuentes et al reported that the hexane extracts of Dictyota ciliolata Sonder ex Kützing (Dictyotaceae), Padina sanctae‐crucis Børgesen (Dictyotaceae), and Turbinaria tricostata E.S. Barton (Sargassaceae) exhibit cytotoxic and antiproliferative activities; however, the compounds responsible for these activities have not yet been identified. Fucosterol and vinylcholesterol were found to be bioactive components of the hexane extracts of T. tricostata and P. sanctae‐crucis , with a CC 50 value of approximately 3.1–25.6 µg mL −1 on the cell lines tested.…”
Section: Biological Effects Of Fucosterolmentioning
confidence: 99%
“…These two component shows anti proliferative effects on different cancer cell lines [54]. Other reports indicate that dichloromethane and ethyl sp.…”
Section: Solieriamentioning
confidence: 99%
“…U937 HL-60 cells [24] Ecklonia cava A2780, SKOV3 [47][48][49][50][51] Laminaria sp Colon , HeLa, colon Ht-29, HTLV [52,53] Padina sp KB, Hep-2, MCF-7, and SiHa [54] Sargassum sp Hela, MDA MB 231. Dalton's Ascitic lymphoma, HepG2, HT-29, Ca co-2, T47D, MDA-MB468 and /NIH 313, [55][56][57][58][59][60] Stypopodium sp SH-SY5Y, RBL-2H3, (Raw267), (V79), Caco-2.…”
Section: Solieriamentioning
confidence: 99%